2019
DOI: 10.1038/s41598-019-40279-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of beta-lactamase genes in diarrheagenic Escherichia coli

Abstract: Beta (β)-lactamases are the most important agents that confer drug resistance among gram-negative bacteria. Continuous mutations in β-lactamases make them remarkably diverse. We carried out the transcriptome analysis of 10 β-lactamase genes of Extended-Spectrum β-lactamases (ESBL), Metallo β-lactamases (MBL), and AmpC β-lactamases (ABL) in drug-resistant and sensitive diarrheagenic E. coli (DEC) isolates obtained from children up to 5 years of age. Out of the 10 β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Moreover, a retrospective study that investigated the development of resistance to antimicrobials in P. aeruginosa showed that imipenem or ciprofloxacin therapy is a key factor of producing resistant strains of P. aeruginosa [ 45 ]. Similarly, it was indicated that the ABR of E. faecium to β -lactams is correlated with possessing the blaZ-blaI-blaR1 operon [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a retrospective study that investigated the development of resistance to antimicrobials in P. aeruginosa showed that imipenem or ciprofloxacin therapy is a key factor of producing resistant strains of P. aeruginosa [ 45 ]. Similarly, it was indicated that the ABR of E. faecium to β -lactams is correlated with possessing the blaZ-blaI-blaR1 operon [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Several genes responsible for antibiotic resistance were also retrieved by computational analysis (Table S2) in Ecc, including β-lactamase-encoding, ABC transporter and efflux system genes (Table S2). In the past two decades, bacteria producing extended-spectrum β-lactamase (ESBL) have been identified mostly from humans and animals samples 11 . ESBLs confer resistance to extended-spe ctrum cephalosporins (ESCs, e.g., ceftriaxone, cefpodoxime, ceftiofur, ceftazidime) and monobactams and often express resistance to non-β-lactam antimicrobials, leaving limited therapeutic options.…”
Section: Genome Wide Gene Prediction and Analysis Of Virulent Genes mentioning
confidence: 99%
“…Moreover, recent studies have shown that in addition to direct killing effects, exposure to antibiotics at subinhibitory concentrations could cause an increase or reduction in the virulence of human and animal bacterial pathogens. The prediction of resistance genes in this pool revealed that Ecc strains are potentially threatening 11 .…”
Section: Genome Wide Gene Prediction and Analysis Of Virulent Genes mentioning
confidence: 99%
“…To analyse the mRNA expression of β-lactamaseand acetyltransferase-encoding genes, total RNA was isolated from the bacteria using TriReagent (Invitrogen, Carlsbad, CA, USA) and converted to cDNA using the a High-Capacity cDNA reverse transcription kit (New England Biolabs, Pickering, Canada). Relative transcript levels of the β-lactamase encoding gene TEM-1 and acetyltransferase encoding gene AAC(3)IV were assayed with an iCycler iQ 5 apparatus (Bio-Rad, Mississauga, Canada) associated with iCycler optical system software (version 3.1) using SYBR Green PCR Master Mix [22][23][24][25]. The mRNA quantification was calculated by using the formula 2 −ΔΔCT , where ΔCT is the difference between the threshold cycle of a given target cDNA and an endogenous reference of 16S rRNA gene.…”
Section: Analysis Of Gene Transcript Levels Of β-Lactamase and Acetylmentioning
confidence: 99%
“…In contrast, the addition of either dandelion root extract or TS brought the activities of these two enzymes to the basal level when compared with the group of cadmium and antibiotic together. To observe whether the altered activities of these enzymes are attributed to their transcriptional changes, we further measured the mRNA expressions of the β-lactamase gene TEM-1 and the acetyltransferase-encoding gene AAC(3) IV [22][23][24][25]. As shown in Fig.…”
Section: Effect Of Dandelion Root Extract and Ts On β-Lactamase And Amentioning
confidence: 99%